Mexico collection
Miscellaneous official documents relating to the Inquisition (1590-1598), the church (1690-1695), the military (1724-1851), emigrants from Louisiana (1803-1811), and the courts (1844-1872).
Collection material in Spanish.
Keywords: Courts -- Mexico; Inquisition -- Mexico; Mexico -- History, Military; Mexico -- Emigration and immigration; Louisiana -- Emigration and immigration; Catholic Church -- Mexico